Correlation of Attitudes towards Remote Consultations of a Rheumatologist with Health Locus of Control: Survey of Lithuanian Patients with Chronic Rheumatic Diseases - Dominykas Antinis; Jurgita Sabaliauskienė (Lithuanian Sports University, 2022)
Background: During the COVID-19 pandemic, telemedicine has become an important means to control the disease with the help of a doctor for patients with chronic diseases. To make treatment of chronic rheumatic diseases effective, it is important that patients have a positive attitude towards the remote consulting and maintained health related individual behavior, which depends on the patient's health locus of control. Methods: The sample of the survey consists of 207 Lithuanian patients with chronic rheumatic diseases. Most of them have been diagnosed with spondyloarthritis (n=83), connective tissue diseases (n=53) and rheumatoid arthritis (n=49). To reveal the attitude towards remote consultations of a rheumatologist, an original questionnaire has been developed, which includes reasons for prioritizing remote consultations of a rheumatologist, and positive and negative attitude towards the consultations. Health locus of control was assessed by Multidimensional Health Locus of Control (MHLC) scale, which contains Internality, Chance and Powerful Others subscales. Results: The survey revealed the main reasons why patients with chronic rheumatic diseases choose remote consultations. When comparing the average of statements revealing positive attitude M=2.78 with the negative one of M=1.51 it becomes obvious that the attitude of subjects towards remote consultations is favorable. A correlation analysis was performed to assess the correlation of patient positive or negative attitudes towards remote consultations with the health locus of control. The results did not establish a correlation between patients' positive attitude towards the named consultations and internality locus of control. However, it has been obtained that a negative attitude towards remote consultations has albeit not strong, but a statistically significant correlation with two indicators of health locus of control - Chance (r=0.203, p≤0.0001) and Powerful Others (r=0.94, p=0.01). Conclusion: The survey revealed a favorable attitude of patients with chronic rheumatic diseases towards remote consultations. Furthermore, it showed that personal conviction of a patient that health depends on circumstances and influence of other people worsens the attitude towards remote consultations. Keywords: telerheumatology, remote consultations, health locus of control.